2021
DOI: 10.24307/psz.2021.0706
|View full text |Cite
|
Sign up to set email alerts
|

Belföldi utazási kedv járványidőszakban a fiatalok körében

Abstract: Magyarországon a turizmus meghatározó gazdasági ágazatot képvisel. A 2020-as COVID-19 pandémia azonban mindent megváltoztatott. Tanulmányunk célja a koronavírus belföldi turizmusra gyakorolt hatásának feltérképezése szekunder és primer adatok által. Kvalitatív kutatás (online mélyinterjúk) alapján feltártuk, hogy a koronavírus nem szegte a fiatalok kedvét a szabadidős célú utazástól és az áremelkedés ellenére sem akarnak lemondani a kikapcsolódás ezen formájáról. Kvantitatív kutatásunk segítségével elvégeztük … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…Based on the type of location, people living in large communities are most likely to want to travel to a safe place (68%), while those living in the capital (53%) and those living in cities and cities with county rights (58%) are less likely to do so. The same results were confirmed in the travel decisions of Hungarian tourists due to COVID, which was confirmed by several Hungarian studies [58,59]. Looking at the travel habits of the respondents, the vast majority of the sample travels most often within Europe, with 876 (92%) indicating a preference for travel within the EU and 266 (27.9%) for travel outside the EU but still within Europe.…”
Section: Methodssupporting
confidence: 77%
See 2 more Smart Citations
“…Based on the type of location, people living in large communities are most likely to want to travel to a safe place (68%), while those living in the capital (53%) and those living in cities and cities with county rights (58%) are less likely to do so. The same results were confirmed in the travel decisions of Hungarian tourists due to COVID, which was confirmed by several Hungarian studies [58,59]. Looking at the travel habits of the respondents, the vast majority of the sample travels most often within Europe, with 876 (92%) indicating a preference for travel within the EU and 266 (27.9%) for travel outside the EU but still within Europe.…”
Section: Methodssupporting
confidence: 77%
“…In our sample, mainly younger and highly educated people were represented from the capital of Hungary, because these strata showed a higher willingness for travelling and were less deterred by the health risk of the COVID pandemic (Table 2). This fact is also supported by several representative domestic studies [29,[57][58][59]. In a nationally representative survey conducted by Csapó-Törőcsik [29] in Hungary (n = 2001), it was found that, in connection with the travel habits of Hungarians, safety is one of the most important factors in choosing a destination and making a travel decision.…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation